2018
DOI: 10.1002/joa3.12028
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmias in nonischemic cardiomyopathy

Abstract: Nonischemic cardiomyopathies (NICMs) are composed of variable disease entities, including primary and secondary cardiomyopathies. Determining the etiology of NICM provides pivotal roles of not only the understanding of the individual pathogenesis, but also the clinical management, such as risk stratification, pharmacological treatment, and intervention therapies. Despite the diverse causes of NICM, these cases mostly require clinical attention owing to progressive myocardial injury, resulting in ventricular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 86 publications
(108 reference statements)
0
17
2
1
Order By: Relevance
“…Cardiovascular magnetic resonance (CMR) offers considerable additional utility beyond LVEF in SSc by allowing the identification of myocardial oedema and fibrosis [ 18 , 19 ], as myocardial fibrosis is the most common substrate for re-entrant arrhythmias [ 20 ]. CMR can thus potentially translate 24 h Holter findings to distinguishable structural myocardial abnormalities functioning as arrhythmogenic foci, as myocardial fibrosis identified by CMR is the most common arrhythmogenic substrate specifically in non-ischaemic cardiomyopathies [ 21 , 22 ], and larger scar extents are associated with increased risk of inducible VT or SCD [ 22 ]. We hypothesized that CMR indices would be independently associated with the occurrence of rhythm disturbances and SCD in SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular magnetic resonance (CMR) offers considerable additional utility beyond LVEF in SSc by allowing the identification of myocardial oedema and fibrosis [ 18 , 19 ], as myocardial fibrosis is the most common substrate for re-entrant arrhythmias [ 20 ]. CMR can thus potentially translate 24 h Holter findings to distinguishable structural myocardial abnormalities functioning as arrhythmogenic foci, as myocardial fibrosis identified by CMR is the most common arrhythmogenic substrate specifically in non-ischaemic cardiomyopathies [ 21 , 22 ], and larger scar extents are associated with increased risk of inducible VT or SCD [ 22 ]. We hypothesized that CMR indices would be independently associated with the occurrence of rhythm disturbances and SCD in SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that MVS patients with a history of CAD showed a trend of better VA recurrence‐free survival compared with those without CAD history (Figure 2B). This could be related to the previously reported different nature of VT circuits between ICM and NICM 43,44 . One observational study compared the characteristics and the outcomes of VT ablation between ICM and NICM patients has shown that complete success and 1‐year VT‐free survival were higher in the ICM group 44 .…”
Section: Discussionmentioning
confidence: 90%
“…(Figure 2B ) This could be related to the previously reported different nature of VT circuits between ICM and NICM. 43,44 One observational study compared the characteristics and the outcomes of VT ablation between ICM and NICM patients has shown that complete success and 1-year VT-free survival were higher in the ICM group. 44 The critical isthmus for VT was identified with endocardial entrainment in 62% of the ICM group and in 17% of the NICM group.…”
Section: Safety and Outcomes Of Ablationmentioning
confidence: 99%